MANAJEMEN SARANA DAN PRASARANA DI SMA NEGERI 3 BANDA ACEH - Prayudi Ginting; Cut Zahri Harun; Bahrun . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Education facilities and infrastructure is one part of the existing management within educational institutions, facilities and infrastructure have a very important role in an organization, institution or educational institution. Without the facilities and infrastructure that support the education process is not running properly. The purpose this study is to find out a complete and accurate of management facilities and infrastructure in SMA Negeri 3 Banda Aceh. The approach this research is qualitative. Instruments this study are interview guides, observation guides, documentation study guide. Data collection techniques are interviews, observation, documentation. The results this study are: (1) Planning facilities and infrastructure is analyzing and selecting needs that accordance with curriculum; (2) The procurement facilities and infrastructure starts from the draft budget approved by the agency based on the available funding sources. Procurement proposals are submitted to education office and other relevant departments and school alumni; (3) Maintenance facilities and infrastructure is by organizing routine maintenance every year, and major maintenance should make a proposal to propose funds the government; (4) Inventory facilities and infrastructure is done by administering inventory based on guidance from local government; (5) The process elimination facilities and infrastructure is done by making the proposal for the elimination of unsuitable goods used submitted to the municipal administration. The conclusion this research is planning facilities and infrastructure is analyzing needs that accordance with curriculum. The procurement facilities and infrastructure starts from the draft budget approved by the agency based on the available funding sources. Maintenance facilities and infrastructure is by organizing routine maintenance every year. Inventory facilities and infrastructure is done by administering inventory based on guidance from local government. The process elimination facilities and infrastructure is done by making the proposal for the elimination of unsuitable goods used submitted to the municipal administration.Keywords: Management, Facilities and Infrastructure.